Inovasi Kebijakan Pengembangan Kota Layak Anak Tangerang Selatan - Disson Muhammad Fauzi; Watriningsih Watriningsih; Bayquni Bayquni (PETANDA: Jurnal Ilmu Komunikasi dan Humaniora, 2020)
This study aims to determine the Development of South Tangerang City Government (Tangsel) Policy implementing the Ministerial Regulation of Women's Empowerment and Child Protection of the Republic of Indonesia Number 11 of 2011 concerning Child Friendly City Development Policies. The research uses a descriptive qualitative approach, which explains the phenomenon in depth through data collection. This descriptive research provides an accurate and objective description and explanation of the actual state of the object under study. The theory used is the theory of public policy making according to Metter and Horn. The results showed that the development of South Tangerang Child Friendly City in general went well. Among them are shown by the achievement of basic health and welfare, the large number of breastfeeding facilities, the high percentage of complete basic immunization for children, the low prevalence of malnutrition in children under five, the low infant mortality rate (IMR), and the active and successful Adolescent Reproductive Health Counseling Information Center.